2011
DOI: 10.1038/hr.2011.205
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and chronic kidney diseases

Abstract: Observational studies have suggested that different chronic kidney diseases (CKDs) have differing relationships to smoking, but no randomized controlled trial has been conducted to examine this topic. In this article, we review available evidence concerning the relationship between smoking and each type of CKD in the general population as well as in patients with diabetes mellitus (DM), hypertension (HT), primary glomerulonephritis and kidney transplants. There is good evidence of a relationship between smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 47 publications
3
39
0
1
Order By: Relevance
“…Consistent with earlier reports, the present data demonstrated that gender, smoking, drinking, proteinuria and eGFR were associated with the kidney survival time of CKD patients (25)(26)(27)(28), which confirmed the validity of the data. The mechanism explained the association among smoking, drinking and CKD progression is that smoking and drinking all contribute to oxidative stress, which plays an important role in the development and progression of CKD (29).…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with earlier reports, the present data demonstrated that gender, smoking, drinking, proteinuria and eGFR were associated with the kidney survival time of CKD patients (25)(26)(27)(28), which confirmed the validity of the data. The mechanism explained the association among smoking, drinking and CKD progression is that smoking and drinking all contribute to oxidative stress, which plays an important role in the development and progression of CKD (29).…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with earlier reports, our data demonstrated smoking and gender were associated with the CKD progression, [29][30][31][32][33] which confirmed the validity of our data. The mechanism explained the relationship between smoking and CKD progression is that smoking contribute to oxidative stress, which plays important role in the development and progression of CKD.…”
supporting
confidence: 82%
“…In addition to hypertension, diabetes mellitus and metabolic syndrome, the incidence of CKD is also closely correlated with unhealthy lifestyle behaviors such as smoking, heavy alcohol intake, obesity, physical inactivity and an unhealthy diet [7][8][9][10][11][12]. Moreover, it is well known that a decreased physical activity and aerobic capacity are predictive factors for the prognosis in ESRD patients [13,14].…”
Section: Introductionmentioning
confidence: 99%